1977
DOI: 10.1172/jci108660
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of antigen- and mitogen-induced human lymphocyte proliferation by gold compounds.

Abstract: A B S T R A C T Gold sodium thiomalate (GST)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(49 citation statements)
references
References 36 publications
3
46
0
Order By: Relevance
“…The data presented here indicate that these concentrations of GST can inhibit lymphocyte activation in vitro. Inhibition occurred even in the presence of optimal concentrations of mitogen, although Lipsky & Ziff (1977) found that inhibition of human lymphocyte activation was more effective when sub-optimal mitogen stimulation was used. Inhibition of both Con A-and LPS-induced activation indicates inhibition of a function necessary for both B and T lymphocyte activation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The data presented here indicate that these concentrations of GST can inhibit lymphocyte activation in vitro. Inhibition occurred even in the presence of optimal concentrations of mitogen, although Lipsky & Ziff (1977) found that inhibition of human lymphocyte activation was more effective when sub-optimal mitogen stimulation was used. Inhibition of both Con A-and LPS-induced activation indicates inhibition of a function necessary for both B and T lymphocyte activation.…”
Section: Discussionmentioning
confidence: 97%
“…Lies, Cardin & Paulus (1977) found that inhibitory effects were not observed if GST was added later than 6 h from the start of the culture. Lipsky & Ziff (1977) also suggested that an early stage of activation was affected, although failure to add GST until 18 h appeared to have no less an effect where less than 100 Mg ml -l GST was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that these compounds suppress accessory cell function of macrophages in local immune responses (24). It may be possible, therefore, that gold compounds regulate local fibroblast proliferation through alteration of macrophage capacity for induction of proliferation of fibroblasts or through inhibition of IL-1 secretion from macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Aurothiomalate (20) and auranofin (19) can inhibit the functional capacity of monocytes to induce T lymphocyte proliferation in vitro. Both …”
Section: Figure 1 Structuresofsome Widely Usedgold Drugsand the Metabmentioning
confidence: 99%